Postharvest application of fungicides, antagonists and plant products for controlling storage scab and rots of apple fruits - R.K. PRASAD; J. KUMAR, K.P. SINGH, AMITABH SINGH (Indian Phytopathology, 2017)
Apple scab (Venturia inaequalis) is widely prevalent in all the season in and around Gangotri valley. Three important commercial cultivars of apple namely, â€˜Red Deliciousâ€™, â€˜Royal Deliciousâ€™, and â€˜Golden Deliciousâ€™ were screened against post-harvest rot causing fungi. Fruits of the cv. Red Delicious developed more scab lesions than those of â€˜Red Deliciousâ€™ and â€˜Golden Deliciousâ€™. Scab lesions gradually increased in all the fruits of Delicious cultivars stored at ambient temperature. The rate of lesion expansion was inversely related to the number of lesions on the fruit. Scabbed fruits showed pronounced shriveling as compared to healthy fruits.Â Other fungal pathogens associated with scab lesion were identified as Trichothecium roseum, Penicillium expansum, Glomerella cingulata, Botrytis cinerea and Monilinia spp. which were responsible for fruit decay in storage. â€˜Red Deliciousâ€™ was highly susceptible to most of the post-harvest pathogens. Postharvest sprays of flusilazole (0.015%) bitertanol (0.075%) and carbandazim (0.05%) were effective in controlling storage scab and other rotting fungi. Biocontrol agents effective against P. expansum and B. cinerea were isolated from apple leaves, and a quantitative relation between antagonists and pathogen inoculum concentration was determined. Bitertanol (0.075%) and Penconazole (0.05%) were highly effective as pre-harvest sprays for inhibiting scab lesions after 30, 45 and 60 days of storage at room temperature. In protective spray programme, propineb (0.4%) was highly effective for storage rot even after 60 days. Thiophanate methyl (0.10%) was effective against development of storage scab and fruit rot. Aonla leaf extract, garlic extract, bitertanol and carbendazim completely inhibited the storage scab and fruit rot up to 60 days during post-harvest dip treatment. It could be suggested that antagonist, plant product and fungicides could make them an excellent treatment for controlling postharvest losses of apple fruits and increase the shelf-life of apple.